Kritik atas Fikih Lintas Agama: Studi atas Pemikiran Kaum Revivalis - Siti Hardianti Liputo; Sofyan A. P. Kau (Al-Mizan (e-Journal), 2019)
This paper explains the revivalist Islamic criticism of the views of the Paramadina Writers Team which permits interfaith marriages and permissibility of inheritance of different religions. This research is a library research with the main data source is the book Fiqh Lintas Agama: Membangun Masyarakat Inklusif-Pluralis. The results showed that Islamic revivalists argued that the history of Mu’azd and Muawiyah which was used as a reference by the Paramadina Writers Team did not agree on its validity compared to the history which forbids a Muslim from inheriting infidels. Whereas giving precedence to an agreed proposition of validity is more important to be held against than an argument whose validity is not agreed upon. Choosing a majority opinion over the opinion of a minority is more prioritized. The case where the majority of scholars forbid interfaith marriages is haram because of the textual statements of the verse, except marriages with the ahl al-kitab. That skill is also an emergency. Even the adverse effects of interfaith marriages must take precedence over benefits.